Strategy for Increasing the Accountability of Waqf Management in Islamic Religious Organizations - Nurhudawi, Nurhudawi; Asmuni, Asmuni; Nasution, Yenni Samri Juliati (Journal of Accounting Research, Organization and Economics, 2024)
Objective This study aims to determine the appropriate accountability conditions and strategies for increasing the accountability of Muslim religious endowment (waqf) institutions managed by religious organizations in North Sumatra, Indonesia.Design/Methodology A qualitative descriptive research method is employed to identify strategies for improving the accountability of waqf management based on the results of in-depth interviews with source persons regarding the issue in North Sumatra.Results Strategies are formulated to increase the accountability of waqf management. These consist of three approaches: synergy between regulators, the Indonesian Waqf Board, and waqf officers (nazirs); the implementation of waqf governance training for nazirs; and the establishment of an Indonesian waqf development master plan.Research limitations/implications The scope of the research sample is confined to waqf management undertaken by religious organizations in North Sumatra, Indonesia. Further study needs to be conducted which considers other waqf organizations such as mosques, as well as the addition of research samples from other regions for comparison. The implication of this research is the need for additional resources that would be useful for the waqf development strategy in order to improve its accountability.Novelty/Originality The novelty of this research is the comparison between waqf accountability and the management strategies of Nahdlatul Ulama (NU) and Muhammadiyah in North Sumatra. Previous research only considered accountability from the perspective of nazirs, whereas this study focuses on strategies to increase the accountability of waqf management of the Nahdlatul Ulama and Muhammadiyah Waqf Institutions in North Sumatra from the perspective of nazirs, students and regulators.